Video Styles and Learning - Beckley, David; Marshall, Jeremy (My University, 2018)
With the current prevalence of online and distance learning, videos are becoming a larger part of our education system. It is important that we be able to fully utilize the potential of videos as education tools. Videos make use of more senses than just printed materials, and provide greater flexibility for both teachers and students (Bevan). What qualities make a good educational video? We believe that to be effective at teaching a video needs to be interesting enough to students’ attention and have enough information to be useful. By surveying a number of college students, we were able to support my hypothesis. With this information, we will be able to better select and create instructional videos both in academia and in the world at large.
Keywords: Fall 2018